Evaluation of the impact of Scottish Reduction in Antimicrobial Prescribing (ScRAP) Programme on GP Practice management of patients with suspected urinary tract infection (UTI). Issue 2 (28th February 2020) - Sneddon, Jacqueline; Thomson, Anne; Cooper, Lesley; Robertson, Ruth
Abstract : Introduction The ScRAP programme was developed as a national initiative to improve management of UTI by optimising use of diagnostic tests and prescribing of antibiotics. It comprised educational content plus improvement ideas, audit tools, good practice guides, patient information and decision aids. Method: A facilitated learning session was delivered, usually by a Prescribing Support pharmacist. All GP Practice staff, both clinical and non-clinical, were invited to attend to promote a team approach to change. Local practice was considered using process mapping and each GP practice completed an action plan with changes they intended to implement. Facilitators and participants were encouraged to complete an on-line feedback survey about the learning session. Action plans from 200 GP Practices in one health board region (21% of Scottish population) were analysed using NVivo 12 software to identify key themes. Results: Completed surveys from facilitators and participants showed both groups were positive about the content, approach and length of the session. Action planning was welcomed as a way to embed learning in practice. Some minor changes to content were suggested. Changes in practice included patient education to promote self-management and a reduction in the number of urine specimens sent to microbiology laboratories. A whole team approach to management of patients with suspected UTI increased the success and impact of the changes made. Conclusion: Evaluation of action plans will be helpful for other GP Practice teams seeking to make improvements. Feedback from facilitators and participants will be used to inform update of the programme content.